Melatonin Attenuates Methamphetamine-Induced Neurotoxicity - Wongprayoon, Pawaris; Govitrapong, Piyarat (Current Pharmaceutical Design, 2016)
Methamphetamine (METH), an illegal psycho-stimulant, is widely known as a recreational drug. In addition to its addictive effect, METH induces neurotoxicity via multiple mechanisms. The major contributors to METH-induced neurotoxicity are reactive oxygen species, which lead to cell death through apoptotic pathway and disturbances in mitochondria, the generation of neuroinflammation, and autophagy. Melatonin, a neurohormone secreted by the pineal gland, is a potent antioxidant compound that plays a beneficial role by protecting against the oxidative stress caused by METH. Melatonin also plays a role in maintaining mitochondrial homeostasis. Nanomolar concentrations of melatonin have been shown to protect against the inflammation caused by METH and to prevent the decrease in neurogenesis caused by METH in progenitor cells obtained from adult rat hippocampal tissue. The intent of this review is to describe the underlying mechanisms involving melatonin that protect against the neurodegeneration caused by METH.
Keywords: apoptosis